A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Kendrick, Gary A.; Nowicki, Robert J.; Olsen, Ylva S.; Strydom, Simone; Fraser, Matthew W.; Sinclair, Elizabeth A.; Statton, John; Hovey, Renae K.; Thomson, Jordan A.; Burkholder, Derek A.; McMahon, Kathryn M.; Kilminster, Kieryn; et al. (Frontiers in Marine Science, 2019)
A central question in contemporary ecology is how climate change will alter ecosystem structure and function across scales of space and time. Climate change has been shown to alter ecological patterns from individuals to ecosystems, often with negative implications for ecosystem functions and services. Furthermore, as climate change fuels more frequent and severe extreme climate events (ECEs) like marine heatwaves (MHWs), such acute events become increasingly important drivers of rapid ecosystem change. However, our understanding of ECE impacts is hampered by limited collection of broad scale in situ data where such events occur. In 2011, a MHW known as the Ningaloo Niño bathed the west coast of Australia in waters up to 4°C warmer than normal summer temperatures for almost 2 months over 1000s of kilometres of coastline. We revisit published and unpublished data on the effects of the Ningaloo Niño in the seagrass ecosystem of Shark Bay, Western Australia (24.6 – 26.6o S), at the transition zone between temperate and tropical seagrasses. Therein we focus on resilience, including resistance to and recovery from disturbance across local, regional and ecosystem-wide spatial scales and over the past 8 yearsThermal effects on temperate seagrass health were severe and exacerbated by simultaneous reduced light conditions associated with sediment inputs from record floods in the south-eastern embayment and from increased detrital loads and sediment destabilisation. Initial extensive defoliation of Amphibolis antarctica, the dominant seagrass, was followed by rhizome death that occurred in 60-80% of the bay’s meadows, equating to decline of over 1000 km2 of meadows. This loss, driven by direct abiotic forcing, has persisted, while indirect biotic effects (e.g. dominant seagrass loss) have allowed colonisation of some areas by small fast-growing tropical species (e.g. Halodule uninervis). Those biotic effects also impacted multiple consumer populations including turtles and dugongs, with implications for species dynamics, food web structure, and ecosystem recovery. We show multiple stressors can combine to evoke extreme ecological responses by pushing ecosystems beyond their tolerance. Finally, both direct abiotic and indirect biotic effects need to be explicitly considered when attempting to understand and predict how ECEs will alter marine ecosystem dynamics.